A3.7 No evidence of cathelicidin being involved in the pathogenesis of lupus and arthritis. (31st January 2014) - Kienhoefer, D.; Schubert, I.; Hahn, J.; Bosch, Èlia; Sjöwall, C.; Agerberth, B.; Schett, G.; Hoffmann, M.
Abstract : Background and Objectives: Antimicrobial peptides (AMPs) such as cathelicidins have a well known role in the immune defence against pathogens. In the last years a contributory impact of AMPs was also reported in the pathogenesis of autoimmune diseases. Therefore, the aim of this project was to examine the impact of cathelicidins on the pathogenesis of lupus and arthritis using animal models and sera from patients. Methods: Pristane-induced lupus (PIL) was induced by intraperitoneal injection of 500 µl pristane (2, 6, 10, 14-tetramethyl-pentadecane) in female C57BL/6 WT and cathelicidin-related antimicrobial peptide (CRAMP -/- ) mice. Autoantibody levels of anti-Sm/RNP, anti-dsDNA and anti-histone were measured via ELISA, serum cytokine levels were determined via FlowCytomix TM Multiplex. Pathological changes in lungs and kidneys isolated from mice at day 14 and 180 after pristane injection were analysed by histology. Collagen-induced arthritis (CIA) was induced in male WT and CRAMP -/- mice and arthritis severity was visually scored. Histomorphometrical analysis was done by OsteoMeasure TM software and included parameters of inflammation, cartilage degradation, and bone erosion. Serum LL-37 and anti-LL-37 levels were measured by ELISA in healthy donors and patients with SLE, RA, and Sjögren syndrome. Results: No differences in the serum-levels of anti-Sm/RNP, anti-dsDNA, and anti-histone autoantibodies or of various cytokines could be observed between WT and CRAMP -/- mice after pristane-injection. Furthermore, the lung and kidney pathology did not differ between WT and CRAMP-deficient mice. Onset of CIA was slightly delayed in CRAMP -/- mice, but at later time points, arthritis incidence or severity was not higher in WT mice compared to CRAMP -/- . Histomorphometry revealed no differences between WT and CRAMP -/- mice. Although serum levels of anti-LL-37 were significantly higher in patients with SLE compared to healthy donors or patients with RA or Sjögren´s syndrome, no correlation to levels of type I Interferons or to disease activity could be observed. Conclusions: Although levels of cathelicidins were upregulated in mouse models of lupus and arthritis, cathelicidin-deficiency did not persistently affect the course of the diseases. Also in patients with SLE, we did not find any evidence that autoantibodies against cathelicidins directly influence disease activity or severity. Reactivity against cathelicidins in lupus and arthritis could thus be an epiphenomenon caused by extensive overexpression in blood and affected tissues. In addition, other cationic AMPs could functionally compensate for the deficiency of cathelicidins.